2016
DOI: 10.1002/ijc.30065
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive disorders of pregnancy and subsequent risk of solid cancer—A nationwide cohort study

Abstract: Women with hypertensive disorders of pregnancy (HDP) have higher levels of antiangiogenic growth factors during pregnancy than women with normotensive pregnancies. Since angiogenesis is necessary for solid cancer growth and spread, we hypothesized that women with a history of HDP might have a reduced risk of solid cancers (cancers other than lymphomas, hematologic cancers and nonmelanoma skin cancers) later in life. In a register-based cohort study of 1.08 million women giving birth at least once between 1978 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…To date relatively few studies have investigated the association between hypertensive disorders of pregnancy and endometrial cancer risk with one study suggesting an increased risk with hypertensive disorders overall64, while another study found no association with preeclampsia overall, although an increased risk was observed with early-onset preeclampsia65. Any further studies could better assess the causality of the observed association between hypertension and endometrial cancer by using genetic risk scores for hypertension6667.…”
Section: Discussionmentioning
confidence: 99%
“…To date relatively few studies have investigated the association between hypertensive disorders of pregnancy and endometrial cancer risk with one study suggesting an increased risk with hypertensive disorders overall64, while another study found no association with preeclampsia overall, although an increased risk was observed with early-onset preeclampsia65. Any further studies could better assess the causality of the observed association between hypertension and endometrial cancer by using genetic risk scores for hypertension6667.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a reduced risk of breast cancer amongst women with a history of preeclampsia, compared with those with normotensive pregnancies . However, the results are not completely consistent and it is unclear whether the anti‐angiogenic imbalance in women who experience preeclampsia is pregnancy‐induced, or if they have an innate tendency towards an anti‐angiogenic response to biological challenge.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…The relationship of other pregnancy characteristics with breast cancer has been studied less often (reviewed in ). To provide some benefit, a full‐term pregnancy appears necessary, as miscarriages do not provide equivalent protection .…”
Section: Pregnancy Characteristics and Maternal Cancer Riskmentioning
confidence: 99%
“…Results here confirm previously reported associations of HDPs without genotype with increased risk for CVD, lower risk for breast cancer, and no change for nonbreast cancer risk. [1][2][3][4][5][6][7][8][9][10][11] Looking at genotype alone, rs2016347 was only associated with all nonbreast cancers, HR, 0.94; 95% CI, 0.90 to 0.98: P¼.01, and although this decrease in risk was relatively small, it was statistically significant for the recessive model and has not been previously reported. Further studies are needed to validate this finding and facilitate the identification of associations with specific cancer sites, which could have significant clinical relevance.…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies have reported differences in certain cancer types, with 2 reporting a decreased risk for lung/respiratory cancers and others reporting an increased risk for endometrial cancer, suggesting that the nonbreast cancer impact of HDP may vary by organ or cell type. [10][11][12] Although HDPassociated cancer and CVD risks may be either competing or additive, the hazard ratio (HR) for all-cause mortality in women with HDP is 1.65 compared with women without HDP, 13 reflecting its major impact on future health.…”
mentioning
confidence: 99%